Research on natural fibre reinforced polymer composites - Salit, Mohd Sapuan (Universiti Putra Malaysia Press, 2009)
This book is about research on natural fibre reinforced polymer composites. Many natural fibres such as oil palm, banana pseudo-stem, coir, coconut shell, sugar palm, kenaf, ramie, jute, sisal, abaca, pineapple leaf, cotton, rise husk and bagasse have been promoted as possible reinforcements in fibre reinforce composites. Natural fibre composite have been reported to be used in various industries such as furniture, automotive and building construction. Research efforts have been intensified in the recent years on various aspects of natural fibre composites such as materials characterization, mechanical, thermal, physical, chemical and environmental properties, and design and manufacture of products made from these materials. The major advantages of these materials include low costs, renewable, abundance, and good specific stiffness and strength properties. In this book, recent research carried out by researchers from Malaysian research institutions and universities on various aspects related to natural fibre polymer composites are reported.